2021
DOI: 10.31557/apjcp.2021.22.7.2259
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude towards Cervical Cancer and Human Papillomavirus among Pharmacists in Japan

Abstract: Objective: The objective of this study was to assess the knowledge and attitude towards cervical cancer and human papillomavirus (HPV) among pharmacists in Japan. Methods: Questionnaires were disseminated to 788 pharmacists employed by the Tsuruha Holdings Inc. A total of 617 pharmacists responded, generating a response rate of 78.3%. Result: Of the 362 females and 255 males, vaccination rates were 14.4% and 0.8%, respectively. In terms of cervical cytology, 35.1% of females received it once every two years, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Only 21.4% and 8.4% obtained a high level of knowledge related to, respectively, HPV and vaccination. Other studies also demonstrated a lack of knowledge regarding HPV vaccination among health professionals [ 62 , 63 , 64 ]. In addition, in our study, higher levels of pharmacist knowledge were positively associated with better attitudes toward HPV vaccination in general, among both girls and boys, and a greater likelihood of advising the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Only 21.4% and 8.4% obtained a high level of knowledge related to, respectively, HPV and vaccination. Other studies also demonstrated a lack of knowledge regarding HPV vaccination among health professionals [ 62 , 63 , 64 ]. In addition, in our study, higher levels of pharmacist knowledge were positively associated with better attitudes toward HPV vaccination in general, among both girls and boys, and a greater likelihood of advising the vaccine.…”
Section: Discussionmentioning
confidence: 99%